Bagunça: marriages and sexuality in tension among kanhgág Indians - Cimbaluk, Lucas (Ilha Revista de Antropologia, 2021)
This article aims to present some aspects of kanhga?g sexuality, addressing what is called bagunc?a, or bagunc?ar, referring behaviors that are seen by some Indians as unruled, especially when talking about younger people in contemporary times. This characterization allows to analyze tensions related to the monogamy, derived from the transformations of the group after contact. In contrast, are presented some non-gamic positions, with celibacy or greater sexual liberty. They represent temporary or more permanent alternatives to notions of marriage and monogamy. From these situations, some comparisons are made with studies of other Je?-Bororo groups and previous references of the specific ethnic group. I read some kanhga?g historical transformations and analyze the bagunc?a as a kind of ritual of passage that precedes the adult life and as a conter-efectuation of monogamy and sexual exclusivity. The article has as ethnographic base the field work realized by the author on kanhga?g villages located in the north of the state of Parana?, southern Brazil, in the region of the Tibagi river basin.